Factors associated with surgical resection in patients with Crohn’s disease: long-term evaluation - Sandro da Costa Ferreira; Lílian Rose Otoboni Aprile; Rogério Serafim Parra; Marley Ribeiro Feitosa; Patrícia Picardi Morais de Castro; Gleici de Castro da Silva Perdoná; Omar Feres; José Joaquim Ribeiro da Rocha; Luiz Ernesto de Almeida Troncon (Acta Cirúrgica Brasileira, 2024)
ABSTRACT Purpose: To evaluate patient characteristics and factors associated with surgical resection in patients with Crohn’s disease (CD). Methods: An analysis was performed on data from 295 patients with CD in follow-up from 2001 to 2018. Medical record data comprised age, gender, location, behavior and duration of the CD, smoking, and extraintestinal manifestation. Patients were divided into two groups according to the presence or absence of surgical resection. Results: Out of the 295 patients with CD, 155 underwent surgical resection (53.2% male, mean age: 43.88 ± 14.35 years). The main indications for surgery were stenosis (44.5%), clinical intractability (15.5%), and intra-abdominal fistulas (15.5%). Smoking (p < 0.001), longer CD duration (p < 0.0001), ileo-colonic location (p = 0.003), stenosing behavior (p < 0.0001), and fistulizing behavior (p < 0.0001) were significantly associated with surgical resection. Initial use of biological was significantly more frequent in the group of patients without surgical resection (p < 0.001). Conclusions: Patients with CD still frequently need surgical treatment. Smoking (current or past), longer disease time, stenosing and fistulizing behavior, and ileo-colonic localization in CD patients were associated with a higher risk of surgery. Awareness about factors associated with unfavorable outcome allows such patients to be treated more appropriately.